2007
DOI: 10.1111/j.1753-6405.2007.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic differences in public opinion regarding water fluoridation in Queensland

Abstract: Objective: To describe public opinion relating to the fluoridation of drinking water in a sample of the Queensland population. Method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…Other fluoridation surveys conducted in Australia to date have also had low response rates. For example, an omnibus telephone survey conducted in Queensland achieved a response rate of only 44%, 20 while a telephone survey in New South Wales obtained a response rate of 46% 36 . Elsewhere, a 2008 telephone survey in Canada only managed a response rate, excluding non‐contacts, of approximately 10%, 37 while a public opinion poll in San Diego, California, USA, in 2006 obtained a response rate of 36.4% 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other fluoridation surveys conducted in Australia to date have also had low response rates. For example, an omnibus telephone survey conducted in Queensland achieved a response rate of only 44%, 20 while a telephone survey in New South Wales obtained a response rate of 46% 36 . Elsewhere, a 2008 telephone survey in Canada only managed a response rate, excluding non‐contacts, of approximately 10%, 37 while a public opinion poll in San Diego, California, USA, in 2006 obtained a response rate of 36.4% 38 .…”
Section: Discussionmentioning
confidence: 99%
“…While it is possible that Queenslanders have different beliefs about water fluoridation than other Australians, several surveys have canvassed only support or opposition for this public health measure, with no comparative studies being undertaken (Local Government Association of Queensland, 2005) 18,19 . The findings almost invariably indicate strong community support for fluoridation in Queensland, with one survey confirming that public approval for fluoridation before implementation correlates with beliefs about associated benefits and harms 20 . However, there is no published study examining differences in beliefs, attitudes or psychological dispositions between Queensland residents and those from the rest of Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of fluoride into the public water system has been highly debated among both the general public and the Queensland Government for many decades. Several surveys conducted in Queensland between 1997 and 2007 show the support for water fluoridation to vary from 60% to 73.4% . Despite claims of public concerns and hesitation to support water fluoridation, an analysis of 405 newspaper portrayals of fluoridation in Queensland from December 2007–July 2010 concluded that fluoridation appeared to generate minimal electoral repercussions…”
Section: Introductionmentioning
confidence: 99%
“…A concentration of research into the attitudes of Australians to CWF has occurred in recent years, 9,11,12,14 presumably because of the widespread coverage of CWF in most states and recent activity extending coverage in Queensland. Recent studies in Australia report higher levels of support for CWF than in this study, and have found that the majority of people support CWF.…”
Section: Oral Healthmentioning
confidence: 99%
“…5,6 Opinion is influenced by a range of factors, including evidence-based information from health authorities and organisations, personal beliefs and heath promotion programs, 5,6 and is also strongly influenced by anti-fluoridation information. 7 While it has recently been reported that more than 90% of NZ dentists support CWF, 8 and overseas reports of public opinion about CWF are available, [9][10][11][12][13][14] there are few scientific reports of the opinions of the NZ public regarding CWF. A 2001 telephone survey of Onehunga residents reported that, while 55% of NZ European respondents were in favour of CWF, only 33% of Māori and Pacific respondents and 38% of Asian respondents were in favour.…”
mentioning
confidence: 99%